Clinical spectrum of pyruvate kinase deficiency: data from the Pyruvate Kinase Deficiency Natural History Study - Grace, Rachael F; Bianchi, Paola; van Beers, Eduard J; Eber, Stefan W; Glader, Bertil; Yaish, Hassan M; Despotovic, Jenny M; Rothman, Jennifer A; Sharma, Mukta; McNaull, Melissa M; Fermo, Elisa; Lezon-Geyda, Kimberly; et al. (Blood, 2018)
An international, multicenter registry was established to collect retrospective and prospective clinical data on patients with pyruvate kinase (PK) deficiency, the most common glycolytic defect causing congenital nonspherocytic hemolytic anemia. Medical history and laboratory and radiologic data were retrospectively collected at enrollment for 254 patients with molecularly confirmed PK deficiency. Perinatal complications were common, including anemia that required transfusions, hyperbilirubinemia, hydrops, and prematurity. Nearly all newborns were treated with phototherapy (93%), and many were treated with exchange transfusions (46%). Children age 5 years and younger were often transfused until splenectomy. Splenectomy (150 [59%] of 254 patients) was associated with a median increase in hemoglobin of 1.6 g/dL and a decreased transfusion burden in 90% of patients. Predictors of a response to splenectomy included higher presplenectomy hemoglobin (P = .007), lower indirect bilirubin (P = .005), and missense PKLR mutations (P = .0017). Postsplenectomy thrombosis was reported in 11% of patients. The most frequent complications included iron overload (48%) and gallstones (45%), but other complications such as aplastic crises, osteopenia/bone fragility, extramedullary hematopoiesis, postsplenectomy sepsis, pulmonary hypertension, and leg ulcers were not uncommon. Overall, 87 (34%) of 254 patients had both a splenectomy and cholecystectomy. In those who had a splenectomy without simultaneous cholecystectomy, 48% later required a cholecystectomy. Although the risk of complications increases with severity of anemia and a genotype-phenotype relationship was observed, complications were common in all patients with PK deficiency. Diagnostic testing for PK deficiency should be considered in patients with apparent congenital hemolytic anemia and close monitoring for iron overload, gallstones, and other complications is needed regardless of baseline hemoglobin. This trial was registered at www.clinicaltrials.gov as #NCT02053480.
Keywords: novorozenec; Infant, Newborn; kombinovaná terapie; hemolytická nesférocytická kongenitální anemie; Infant; Humans; genetické asociační studie; kojenec; lidé středního věku; Pyruvate Kinase; dítě; Anemia, Hemolytic, Congenital Nonspherocytic; Child; Female; mutace; cholecystektomie; dospělí; mladý dospělý; Phenotype; výsledek terapie; Genotype; lidé; Enzyme Activation; Pyruvate Metabolism, Inborn Errors; předškolní dítě; určení symptomu; Adult; Cholecystectomy; ženské pohlaví; Blood Transfusion; Genetic Association Studies; Male; vrozené poruchy metabolismu pyruvátu; Middle Aged; fenotyp; Adolescent; Treatment Outcome; splenektomie; Young Adult; genotyp; krevní transfuze; aktivace enzymů; Combined Modality Therapy; mužské pohlaví; pyruvátkinasa; Child, Preschool; Mutation; Splenectomy; mladiství; Symptom Assessment